ANALISIS KEUNTUNGAN USAHA PEMBUATAN TAHU PADA UD. MAKMUR SENTOSA DI KOTA MANADO - Naswan Indra Santho Antarani; Leonardus Ricky Rengkung; Ribka Magdalena Kumaat (AGRI-SOSIOEKONOMI, 2019)
This study aims to determine the benefits of tofu industry. This research was conducted at the tofu factory UD Makmur Sentosa in Kleak Urban Village, Hamlet V, Malalayang Sub-district, Manado City. The data collection method in this study used primary data collected through direct interviews with 2 business owners (husband and wife) and the entire workforce of 5 workers based on a list of questions prepared previously. Total respondents were 7 people. Secondary data obtained from the internet through Google Scholar to get articles from various scientific journals and theses from other universities related to research topics on the Profit of the business of Tofu Factory. Data collected in the form of data characteristics of business actors, raw materials, production, capital, and production costs. Tofu business UD. Makmur Sentosa is a small business that began operating in 2000 using its own capital. The amount of soybean raw material used in one month is 7,910 kg and produces 1,582 buckets of tofu, and produces a profit of Rp.41,811,780. So getting an R / C ratio> 1 is 1.49, it means that in March 2019 the UD tofu business. Makmur Sentosa experienced profits so this business was worth the effort.*eprm*